واقع الاتصال الااداري في المؤسسات الاستشفائية - فاطمة الشناف; زينب قاوي; د/ حرزالله شوشة (جامعة عمار ثليجي الاغواط, 2024)
 ملخص الدراسة: تهدف هذه الدراسةإلى معرفة وسائل الاتصال الإداري التي تستخدم في المؤسسة الإستشفائية هواري بومدين بقصر الحيران – الأغواط، وإلى مدى فاعلية الاتصال الإداري في انسياب المعلومات داخل المؤسسة، كما تهدف أيضا إلى معرفة أهم معيقات الاتصال الإداري التي تواجه الموظفين في المؤسسة. وكان مجتمع دراستنا يتكون موظفين المؤسسة الإستشفائية هواري بومدين بقصر الحيران – الأغواط، معتمدين على العينة القصدية وتمكنا من الوصول لهم عبر الاستبيان،كانت مدة الدراسة مابين شهري ديسمبر 2023وأفريل 2024. - توصلت الدراسة للعديد من النتائج أهمها: وسائل الاتصال الموجودة في المؤسسة الإستشفائية هواري بومدين بقصر الحيران هي البريد الإلكتروني والاجتماعات، الهاتف والفاكس، وتستخدم هذه الوسائل في إعطاء الأوامر ونقل المقترحات،المعلومات التي يتلقها أفراد العينة من خلال هذه الوسائل هي واضحة. يتم الاتصال بأفراد العينة لتقديم توجيهات ونصائح عن العمل وإعلام العمال بالقرارات الجديدة،والوسائل الأكثر فعالية في الاتصال الإداري هي الاجتماعات والبريد الإلكتروني.  Study summary: This studyaims to know the administrative communication methodsthat are used in the Houari Boumediene HospitalFoundation in Kasr El Hiran - Laghouat, and to whatextent administrative communication is effective in the flow of information within the institution. It alsoaims to know the most important administrative communication obstacles facingemployees in the institution. Our study population consisted of employees of the Houari Boumediene HospitalFoundation in Ksar El Hiran - Laghouat, relying on a purposivesample and wewere able to reachthemthrough a questionnaire. The studyperiodwasbetween the months of December 2023 and April 2024. The studyreachedmanyresults, the most important of which are: The means of communication available at the Houari Boumediene Hospital Institution in Kasr El Hiran are e-mail, meetings, telephone, and fax. Thesemeans are used to giveorders and conveyproposals. The information that the samplemembersreceivethroughthesemeansisclear. Samplemembers are contacted to provide guidance and advice about work and to informworkers of new decisions. The most effective means of administrative communication are meetings and e-mail.
دراسة ميدانية على عينة من موظفي المؤسسة الاستشفائية هواري بومدين بقصر الحيران الاغواط